Interfacial Microstructures and Mechanical Properties of TiC Reinforced GH 3230 Superalloy Manufactured by Laser Metal Deposition - Yan Wang; Neng Li; Wei Liu; Chonglin Jia; Yu Wu; Chao Gao; Huaping Xiong (Chinese Journal of Mechanical Engineering)
Abstract GH 3230 superalloy is a solution strengthening nickel-based superalloy and it is commonly used for fabricating hot components with the service temperature of above 900 ℃. In order to further improve high-temperature performance, nickel-based alloy matrix composites (NMCs) were proposed. Meanwhile, it is known that laser additive manufacturing is an optional method for fabricating nickel-based composites. However, the research on ceramic-reinforced GH 3230 fabricated by laser metal deposition (LMD) are highly lacking. The aim of this study is to develop TiC ceramic particle reinforced GH 3230 composites using laser metal deposition (LMD) method and study the effect of TiC content on their microstructure and tensile properties. The results showed that TiC particles not only changed the intensity and position of the X-ray diffraction peaks of the alloy matrix but also had a significant effect on the refinement of the cellular dendrites. Meanwhile, it was found that an interfacial layer with sub-micrometer thickness was formed between the TiC ceramic particle and the superalloy matrix, which was identified to be (W, Ti)C1-x phase by the TEM. In terms of the as-built composites, the ultimate tensile strength (UTS) and yield strength (YS) gradually increased, but elongation (EL) decreased with the increase of TiC content. For the as-LMDed 10 vol.% TiC/GH3230 composites, UTS and EL reached 1077.0 MPa and 12.4%, respectively. The enhancement of the tensile strength for composites was attributed to the combined effect of grain refinement strengthening, Orowan strengthening, dislocation strengthening and loading-bearing strengthening.